2012
DOI: 10.1002/zamm.201200020
|View full text |Cite
|
Sign up to set email alerts
|

Raman microprobe spectrometry of carbon/carbon composites with differently‐textured pyrolytic carbon matrices

Abstract: The microstructure of carbon/carbon composites obtained by chemical vapor infiltration of carbon-fiber felts was studied comparatively by means of Raman spectroscopy, polarized light microscopy (PLM), scanning electron microscopy (SEM), and X-ray diffraction. The matrices, which are homogeneously textured according to PLM, exhibit pronounced spatial structural gradients at the sub-μm scale if investigated by means of Raman microprobe spectrometry. The Raman and SEM observations demonstrate that the high-temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The intensity of the D band relative to that of the G band increases with the degree of disorder. Furthermore, D4 and D3 bands are observed that occur in high-defect carbons such as carbon black and have been assigned to the presence of amorphous carbon (D3) and of hydrocarbon or aliphatic moieties bonded to graphitic basic structural units (D4). ,, …”
Section: Resultsmentioning
confidence: 99%
“…The intensity of the D band relative to that of the G band increases with the degree of disorder. Furthermore, D4 and D3 bands are observed that occur in high-defect carbons such as carbon black and have been assigned to the presence of amorphous carbon (D3) and of hydrocarbon or aliphatic moieties bonded to graphitic basic structural units (D4). ,, …”
Section: Resultsmentioning
confidence: 99%